2002
DOI: 10.1175/1520-0493(2002)130<2110:teovws>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vertical Wind Shear on the Distribution of Convection in Tropical Cyclones

Abstract: The influence of vertical wind shear on the azimuthal distribution of cloud-to-ground lightning in tropical cyclones was examined using flash locations from the National Lightning Detection Network. The study covers 35 Atlantic basin tropical cyclones from 1985-99 while they were over land and within 400 km of the coast over water. A strong correlation was found between the azimuthal distribution of flashes and the direction of the vertical wind shear in the environment. When the magnitude of the vertical shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
201
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(256 citation statements)
references
References 34 publications
40
201
0
Order By: Relevance
“…By contrast, corresponding uniform-flow experiments tend to produce more symmetric rainfall pattern (not shown), suggesting that the ambient vertical shear is responsible for the asymmetric convective heating. Previous modeling studies with convective heating (Wang and Holland 1996a;Bender 1997), and observational studies (Franklin et al 1993;Corbosiero and Molinari 2002;Black et al 2002) also suggest that convective asymmetries in tropical cyclones are closely related to vertical wind shear. Frank and Ritchie (2001) speculated that differential vorticity advection with height caused by the shear could be the mechanism responsible for the asymmetry.…”
Section: Simulated Tracksmentioning
confidence: 87%
See 1 more Smart Citation
“…By contrast, corresponding uniform-flow experiments tend to produce more symmetric rainfall pattern (not shown), suggesting that the ambient vertical shear is responsible for the asymmetric convective heating. Previous modeling studies with convective heating (Wang and Holland 1996a;Bender 1997), and observational studies (Franklin et al 1993;Corbosiero and Molinari 2002;Black et al 2002) also suggest that convective asymmetries in tropical cyclones are closely related to vertical wind shear. Frank and Ritchie (2001) speculated that differential vorticity advection with height caused by the shear could be the mechanism responsible for the asymmetry.…”
Section: Simulated Tracksmentioning
confidence: 87%
“…However, there is no consensus about the role of convective asymmetries in tropical cyclones. Corbosiero and Molinari (2002) speculated, based on their observational study, that asymmetric convection is excited so as to minimize tropical cyclone tilt in the inner core. On the other hand, Wu and Wang (2001, hereafter referred to as WW) and Chan et al (2002) argued that convective asymmetries could play an active role in TC motion, rather than a mere response to vertical shear.…”
Section: Introductionmentioning
confidence: 99%
“…A number of observational (e.g., Franklin et al 1993;Gamache et al 1997;Black et al 2002;Corbosiero and Molinari 2002, 2003), and modeling (e.g., Bender 1997Frank and Ritchie 2001;Rogers et al 2003;Ueno 2003) studies have shown a tendency for typhoonstrength vortices to develop upward motion, and/or produce precipitation, particularly in the eyewall, on the down-shear to downshearleft side of the storm. Among the observational studies, the most extensive one is the work of Corbosiero and Molinari, that used groundbased lightning data to evaluate the convective activities around TCs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Pastushkov, 1975;Corbosiero and Molinari, 2002;Lang et al, 2007;Ueno, 2007). The delayed initiation of convection is associated with a strong vertical wind shear (e.g.…”
Section: Introductionmentioning
confidence: 99%